Effect of a single low-dose esketamine administration during surgical abortion on postoperative sleep disturbance: a randomized controlled trial - Zhenhua Song; Miao Miao; Fei Huang; Lingyue Hu; Xinyu Yang; Wei Cui; Yonghao Yu; Guolin Wang; Chunyan Wang; Linlin Zhang (Nature Communications)
Abstract Women with pre-existing sleep disturbance frequently experience postoperative sleep disturbance after surgery. This randomized, double-blind, placebo-controlled, parallel-group trial was conducted to investigate the efficacy of intraoperative adjunctive esketamine administration in the reduction of postoperative sleep disturbance following surgical abortion for women with pre-existing sleep disturbance. 204 women who had sleep disturbance and were scheduled for elective surgical abortion were randomized in a one-to-one allocation ratio to receive either a single intravenous injection of 0.2 mg/kg of esketamine or placebo (saline) immediately after the beginning of surgery (102 women allocated to each group). This trial has now completed. The primary outcome, incidence of sleep disturbance on the first night after surgery, is significantly lower in the esketamine group than in the placebo group (47.1% [48 of 102] vs 71.6% [73 of 102]; odds ratio, 0.35; 95%CI, 0.20–0.64; P = 0.0004). No treatment-related serious adverse events were observed. Here we show that a single low dose of esketamine during surgical abortion improves postoperative sleep quality for women with pre-existing sleep disturbance. ClinicalTrials.gov identifier: NCT06388824.